2006
DOI: 10.1111/j.1365-2303.2006.00397.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐guided fine needle aspiration cytology in the diagnosis and management of thyroid nodules

Abstract: Ultrasound-guided FNAC has a significantly lower yield of inadequate aspirates than palpable FNAC. The ability of FNAC to predict neoplasia in 89% patients and to exclude neoplasia in 95.9% patients makes an important contribution to the multidisciplinary assessment of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
60
1
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 20 publications
(61 reference statements)
5
60
1
5
Order By: Relevance
“…Considering that 187 of the 558 thyroid nodules (33.5%) were smaller than 1 cm, the rate of inadequate sampling for USgFNAC was low. In addition, after histopathologic examination, the positive predictive value of USgFNAC in our study was 90.2%, indicating that our procedure was more sensitive and accurate than in previous reports [10,12].…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…Considering that 187 of the 558 thyroid nodules (33.5%) were smaller than 1 cm, the rate of inadequate sampling for USgFNAC was low. In addition, after histopathologic examination, the positive predictive value of USgFNAC in our study was 90.2%, indicating that our procedure was more sensitive and accurate than in previous reports [10,12].…”
Section: Discussioncontrasting
confidence: 46%
“…Previously, the rate of inadequate sampling for FNAC done "freehand" was 11-13% [10,11,15]. More recent studies using USgFNAC have reported rates of 6-7.2% [10,12,13]. Although the mean tumor size in our study was 16.4 ± 11.3 mm, we performed USgFNAC on all tumors larger than 3 mm.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The differences described above in epidemiological situations of examined populations result in significant differences in the reported data on FP and FN results, as well as sensitivity (from 65 to 99%) and specificity (from 72 to 100%) of thyroid FNAB (30,(35)(36)(37)(38)(39)(40).…”
Section: Second Version (%)mentioning
confidence: 99%
“…First, criteria used to determine adequacy of thyroid FNAC vary in the literature, 15,20 and in some other studies, lower numbers of follicular cells were required to reach adequacy in colloid nodules or cysts. 21,22 In our study, 5 to 6 groups, each with 10 or more benign cells, were required to reach adequacy; this also applied to pure cystic or colloid nodules. This is in accord with the Bethesda system for thyroid FNAC, which recommends that FNAC obtained from cysts and comprising pure colloid or macrophages without follicular cellular elements be reported as nondiagnostic/unsatisfactory followed by the subcategory cyst fluid only.…”
mentioning
confidence: 99%